Studi Randomized Clinical Trial (RCT) Terapi Gizi pada Anak dengan ADHD: Literature Review: Randomized Clinical Trial (RCT) Study of Nutrition Therapy in Children With ADHD: Literature Review - Miladitiya, Aulia (JURNAL GIZI DAN KESEHATAN, 2024)
Attention-Deficit/Hyperactivity Disorder (ADHD) is a neurological behavioral problem seen in children, associated with learning disorders, impulsive behavior, hyperactivity, and inability to concentrate. Global Burden of Disease data in 2019 shows that the highest prevalence of children with ADHD aged 10-14 years is 2.9%. Adjusting diet and nutrition is a consideration to improve ADHD symptoms. This literature review aims to determine macro and micronutrients that have benefits in nutritional therapy for children with ADHD based on the results of RCT studies. The review was carried out by searching the literature on the PubMed database with the keywords "Nutrition Therapy", "ADHD", and "children". The results of the literature search obtained a total of 305 articles in the database, and 4 articles met the review criteria. The results of the literature review show that the macronutrient essential fatty acids (EPA) at a dose of 1.2 g is useful for nutritional therapy in children aged 6-18 years with ADHD through cognitive improvement. Micronutrients vitamin D3 2000 IU/day and magnesium 6 mg/kg BW/day can improve behavioral function and mental health and increase serum 25(OH)D levels in children with ADHD. Macronutrient (EPA) and micronutrient (vitamin D and magnesium) interventions in the form of supplementation play a role in reducing ADHD symptoms based on RCT studies.   ABSTRAK Attention-Deficit/Hiperactivity Disorder (ADHD) merupakan masalah perilaku terkait dengan saraf yang terlihat pada anak-anak, berkaitan dengan gangguan belajar, perilaku impulsif, hiperaktivitas dan tidak dapat memusatkan perhatian. Data Global Burden of Disease tahun 2019 menunjukkan prevalensi anak dengan ADHD paling tinggi usia 10-14 tahun sebesar 2,9%. Pengaturan pola makan dan gizi menjadi pertimbangan untuk memperbaiki gejala ADHD. Tujuan literature review ini untuk menentukan zat gizi makro dan mikro yang mempunyai manfaat dalam terapi gizi anak dengan ADHD berdasarkan hasil studi RCT. Review dilakukan dengan penelusuran literature pada database PubMed dengan kata kunci “Nutrition Therapy”, “ADHD”, “children”. Hasil penelusuran literature memperoleh sejumlah 305 artikel pada database, dan yang memenuhi kriteria review sejumlah 4 artikel. Hasil literature review menunjukkan bahwa zat gizi makro asam lemak esensial (EPA) dosis 1,2 g bermanfaat untuk terapi gizi pada anak usia 6-18 tahun dengan ADHD melalui perbaikan kognitif. Zat gizi mikro vitamin D3 2000 IU/hari dan magnesium 6 mg/kg BB/hari dapat memperbaiki fungsi perilaku dan kesehatan mental serta meningkatkan kadar 25(OH)D serum pada anak dengan ADHD. Intervensi zat gizi makro (EPA) dan zat gizi mikro (vitamin D dan magnesium) dalam bentuk suplementasi berperan dalam mengurangi gejala ADHD berdasarkan studi RCT.